Kwestia miary. O pierwszych odczytaniach „Zygmunta Augusta” Lucjana Rydla - Kowalczuk , Urszula (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
The paper presents an early literary critical reception of ’Zygmunt August’, a trilogy by Lucjan Rydel. The analysis includes, above all, reviews whose subject is a literary work as whole, rather than its particular sections. It has been proven that critical remarks on Rydel’s work could be included in the discussion on the possibilities and needs of the Polish historical drama. The most essential problems of the text revolve around the difficulties connected with finding the right assessment and description criteria of Rydel’s work by professional readers. They were situated either against the pattern of national drama, or it was qualified as a popular drama. Some crucial discrepancies related to ‘measure,’ according to which Rydel’s work should be evaluated, also appeared, depending on whether it was treated as a drama or ‘performance.’